2020
DOI: 10.1186/s40814-020-0561-z
|View full text |Cite
|
Sign up to set email alerts
|

Standard care informed by the result of a placental growth factor blood test versus standard care alone in women with reduced fetal movement at or after 36+0 weeks’ gestation: a pilot randomised controlled trial

Abstract: Background: Biomarkers of placental function can potentially aid the diagnosis and prediction of pregnancy complications. This randomised controlled pilot trial assessed whether for women with reduced fetal movement (RFM), intervention directed by the measurement of a placental biomarker in addition to standard care was feasible and improved pregnancy outcome compared with standard care alone. Methods: Women aged 16-50 years presenting at eight UK maternity units with RFM between 36 +0 and 41 +0 weeks' gestati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…47 A second RCT (n=216) compared standard care and a biomarker blood test (ratio of soluble fms-like tyrosine kinase-1 to placental growth factor), with the result of the blood test indicating whether expedited birth was offered, with standard care alone in presentations with RFM after 36 weeks' gestation. 41 No data for our primary outcome of stillbirth were reported; we did not pool data for secondary analyses because of differences in the interventions. Effect sizes for secondary outcomes can be seen in Supplemental File S4.…”
Section: Effect Of Encouraging Awareness Of Fetal Movement On Perinat...mentioning
confidence: 99%
“…47 A second RCT (n=216) compared standard care and a biomarker blood test (ratio of soluble fms-like tyrosine kinase-1 to placental growth factor), with the result of the blood test indicating whether expedited birth was offered, with standard care alone in presentations with RFM after 36 weeks' gestation. 41 No data for our primary outcome of stillbirth were reported; we did not pool data for secondary analyses because of differences in the interventions. Effect sizes for secondary outcomes can be seen in Supplemental File S4.…”
Section: Effect Of Encouraging Awareness Of Fetal Movement On Perinat...mentioning
confidence: 99%
“…Biomarkers for placental function may hold the key to identifying those pregnancies truly at risk of adverse outcomes, allowing for individualised care and reduction in intervention; however, at present, there is insufficient evidence to make a judgement regarding the efficacy of this approach [71]. Initial studies of the implementation of sFlt-1/PlGF ratio suggest that using biomarkers to determine requirement for or the timing of intervention is feasible [72]. More research and intervention trials in this area will not only address the priorities identified in the recent Saving Babies' Lives Care Bundle but will help further develop guidance on the management of the SGA fetus [36].…”
Section: Discussionmentioning
confidence: 99%